2018
DOI: 10.1021/acs.energyfuels.7b03129
|View full text |Cite
|
Sign up to set email alerts
|

Ash–Bed Material Interaction during the Combustion and Steam Gasification of Australian Agricultural Residues

Abstract: The time-dependent layer-formation process of the agglomerates for three common agricultural residues in Australia with different ash-forming elements, together with quartz sand as the bed material, were investigated in a lab-scale, fixed-bed reactor under combustion (5% v/v O 2 ) and steam-gasification (50% v/v steam) atmospheres at 900 °C. The impact of the atmosphere on the ash−bed material interaction was studied from the elemental composition and the morphology of the agglomerates, which were characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 43 publications
3
40
2
Order By: Relevance
“…While studies referring to industrial-scale plants mainly focused on olivine as a bed material [26], several alternative bed materials have been studied in lab-to pilot-scale experiments, where an activation could be observed [16,17,27,28]. Studies have shown that the layer formation during (steam) gasification is comparable to layer formation during combustion [29,30]. Only fuels rich in sulfur lead to different layers and agglomerates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While studies referring to industrial-scale plants mainly focused on olivine as a bed material [26], several alternative bed materials have been studied in lab-to pilot-scale experiments, where an activation could be observed [16,17,27,28]. Studies have shown that the layer formation during (steam) gasification is comparable to layer formation during combustion [29,30]. Only fuels rich in sulfur lead to different layers and agglomerates.…”
Section: Introductionmentioning
confidence: 99%
“…Only fuels rich in sulfur lead to different layers and agglomerates. During combustion, sulfur is retained in the ash to form various sulfates, while it is released in the gas phase during gasification [29]. More potassium and sodium are then available to react with the bed material to form, e.g., low-melting silicates in the case of a quartz bed.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism (c) describes the direct adhesion of partly molten ash-derived potassium silicate particles on bed particles. These mechanisms have been found to be suitable to describe the occurring phenomena [10,13,15] and were further developed for various biomass fuels [7,16].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the observed problems of agglomeration and deposition formation with quartz beds [7,16,17], several alternative bed materials, like olivine [6], K-feldspar [6], magnesite [17][18][19], calcite [18,19], dolomite [17], sillimanite [18], bauxite [18], and plagioclase [6], were tested for their suitability in fluidized bed applications. Further studies on K-feldspar focused on the layer formation in combustion [14] and gasification atmosphere [12], or a direct comparison of both [20].…”
Section: Introductionmentioning
confidence: 99%
“…First insights into ash layer formation in both combustion and gasification [15,16] have been reported, indicating that the operational mode has no influence on the layer formation, apart from S-rich feedstocks, where the formation of a melt only occurring during combustion enhances the agglomeration tendency of S-rich feedstocks [15]. The influence of P on the layer formation has been studied in combustion [2] and gasification [17] atmosphere, but to the authors' knowledge no study focused on a comparison of P-rich feedstocks in both combustion and gasification atmosphere.…”
Section: Introductionmentioning
confidence: 99%